Institutional changes to reduce land preparation delay in the North Central Province of Sri Lanka - Loeve, Ronald; Somaratne, Pallewatte G.; Ariyaratne, Badugodahewa Ranjith; Anputhas, Markandu; Jinapala, Kiribandage (International Water Management Institute, 2004)
Although many irrigation systems in the dry zone of Sri Lanka have water shortage problems, water consumption is very high during land preparation. This paper analyzes the impact of institutional interventions on efficient water management, especially during the land preparation period. It provides a comprehensive understanding of the factors behind prolonged periods of land preparation so that system managers and farmers communities can develop appropriate interventions to reduce water consumption